[PP.19.08] SERUM URIC ACID CHANGE AND MODIFICATION OF BLOOD PRESSURE AND FASTING PLASMA GLUCOSE IN A PHARMACOLOGICALLY UNTREATED POPOLATION SAMPLE: DATA FROM THE BRISIGHELLA HEART STUDY. (September 2016) - Cicero, A.F.G.; Rosticci, M.; Fogacci, F.; Parini, A.; Urso, R.; Grandi, E.; D'Addato, S.; Borghi, C.
Abstract : Objective: Serum uric acid (SUA) is an emerging risk factor for incident hypertension and type 2 diabetes. Our ais is to clarify if changes in SUA are associated to different incidence in these main cardiovascular risk factors in a general population sample. Figure. No caption available. Design and method: For the purpose of this study, from the historical cohort of the Brisighella Heart Study, a longitudinal epidemiological study, we selected non diabetic subjects that in 2008 were untreated with uric acid lowering drugs nor antihypertensive ones, and that in the following 4 years did not suffer from gout, stage IV-V chronic kidney disease, neoplasms or used in non continuous way uric acid lowering drugs. Then we divided the subjects in four main groups: the ones that mantained their SUA level unchanged during the next 4 years, the ones that increased it >1 mg/dL without treatment, the ones that reduced it >1 mg/dL without drug treatment and the ones that reduced it >1 mg/dL with the continuous use of allopurinol (150–300 mg/day). Results: As expected, in the whole population, BMI, BP, FPG, Glucose, total and LDL-cholesterol, and TG had the tendence to increase with the increase of age between the two consecutive population surveys. However, evaluating the trend in the various studied parameters among the different identified subgroups, we observed specific differences only as it regards SBP and FPG. Infact, no significant changes have been registered as it regards anthropometric measurement, lipid pattern, liver and renal function in the different considered population subgroups. Compared to 2008, SBP significantly increased in subjects with worsened (and untreated) SUA level, while improved in subjects treated with allopurinol. In 2012, subjects with worsened (and untreated) SUA level had a significantly higher SBP compared with subjects with unchanged SUA and those with SUA improved after allopurinol treatment (p < 0.05). An identical trend has been observed as it regards FPG. Conclusions: Based on our data, obtained from a cohort of overall healthy subjects, it seems that the SUA control could positively influence the age-related worsening of SBP and FPG in general population.